Gender Stereotypes and Green Banking Toward Carbon-Free Economy - Tetyana Pimonenko; Oleksii Lyulyov; Yana Us; Oleksii Dubyna; Osei Owusu Evelyn Kumah (Financial Markets, Institutions and Risks)
The concept of modern world ideology accepts that sustainable development goals couldn’t be achieved without green restructure and gender equality. That is the base of the new green economy focused on the social welfare of living and future generations due to increasing the eco-efficiency. This paper summarizes the arguments and counterarguments within the scientific discussion on gender stereotypes in society and green banking. Systematization of scientific sources and approaches concerning the investigated issues showed that only several international financial funds and organizations established in response to climate change focus on the gender aspects towards empowering women with more opportunities to participate in green projects. The primary purpose of the research is to determine how finance and gender determinants influence the carbon-free economic transformation. To gain the research goal, this study applied the modified Cobb-Douglas function that utilizes cross-sectional data on green finance and gender determinants. The methodological tool of this research is the method of least squares. The research object is Ukraine and the Visegrad countries (Poland, Slovak Republic, Czech Republic, and Hungary). The empirical results showed that the women employed in services, GDP, the share of female population, and level of female unemployment have statistically significant impacts on carbon-free economic development. In contrast, foreign direct investment and women in national parliaments are insignificant. Therefore, the research empirically confirmed and theoretically proved that gender equality impacts carbon-free economic development. The main research limitation is the lack of open-access data to monitor the green financial activity under gender equality consideration.